Idiopathic intracranial hypertension and organ of vision - Mrugacz, Małgorzata; Szumiński, Michał (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Idiopathic intracranial hypertension (IIH) is defined as a syndrome of increased intracranial pressure without causative lesions on magnetic resonance imaging. The symptoms of IIH patients are headache, transient visual obscurations, photopsia, retrobulbar pain, diplopia, visual loss and papilledema. Management of intracranial hypertension is initially medical, using a combination of managed weight body reduction and diuretic, non-steroid and steroid therapy. Surgical therapy may be required to stabilize vision.